Toward a Molecular Classification of Colorectal Cancer: The Role of BRAF - Thiel, Alexandra; Ristimäki, Ari (Frontiers in Oncology, 2013)
Different genetic aberrations of BRAF have been reported in various malignancies. BRAF is member of the RAS/RAF/MEK/ERK pathway and constitutive activity of this pathway can lead to increased cellular growth, invasion, and metastasis. The most common activating BRAF mutation in colorectal cancer is the V600E mutation, which is present in 5-15% of all tumors, and up to 80% of tumors with high microsatellite instability harbor this mutation. BRAF mutation is associated with proximal location, higher age, female gender, MSI-H, high grade, and mucinous histology, and is a marker of poor prognosis in colorectal cancer. The role of BRAF mutation as a predictive marker in respect of EGFR targeted treatments is controversial. BRAF V600 selective inhibitors have been approved for the treatment of V600 mutation positive metastatic melanoma, but the response rates in colorectal cancer are poor. This might be due to innate resistance mechanisms of colorectal cancers against the treatment solely targeting BRAF. To overcome resistance the combination of treatments, simultaneous inhibition of BRAF and MEK or PI3K/mTOR, might emerge as a successful therapeutic concept.